První nálezy Giardia spp. u koní v Ceské republice - Pavlásek, I; Hess, L; Stehlík, I; Stika, V (Veterinarni medicina, 1995)
The first occurrence of Giardia spp. in horses in the Czech Republic is reported. During preventive examination of 360 five-month up to 14-year horses from various parts of the region of Central Bohemia carried out from January 1993 to June 1994 in the parasitological laboratory of the State Veterinary Institute in Prague, the Giardia cysts were detected in the excrements of 18 (5%) horses, mostly 2-4 years of age, and in two foals 3 and 6 weeks old. During the period between March 1993 and June 1994, systematic and repeated observation was aimed at a group of 38 racing horses two up to four years of age from two studs in the surroundings of Prague. In one of these studs Giardia spp. cysts were found in 7 horses (35%) out of a total of 20 animals. During bacteriological examination of horses infected with Giardia carried out parallely, only in one animal pathogenic bacteria Rhodococcus equi and Streptococcus equi subsp. zooepidemicus were detected in the excrements. After the application of Entizole (following discontinuation of the preparation on days 4 and 50), however, the result of bacteriological examination was negative. The size of cysts (n = 100) was 12.8-16.0 x 9.6-11.2 microns (with the mean of 14.6 x 9.9 microns) there was no finding of free trophozoites of Giardia in the horse excrements examined. On the basis of morphological characteristics of the protozoon cysts and of the structure of median bodies (following excystation of the Giardia cysts in vitro), the intestinal flagellate found in horses can be included into the morphological group of G. intestinalis.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: giardiáza; Czech Republic; Horse Diseases; koně; Horses; Česká republika; zvířata; nemoci koní; mužské pohlaví; Male; Animals; Giardiasis